Demystification of corporate independence theory in comparative law (2015)
The article examines the evolution of the common law theory of corporate personality and its accompanying benefits. By reference to empirical analysis, the paper explores the exceptions that have been made to the corporate independence theory by the legislature and the common law courts in comparative law. A succinct appraisal of those exceptions is made and it is concluded that the benchmark for ignoring the concept of corporate personality judging especially from the decisions of the courts has not followed any consistent pattern. The paper therefore argues for a need to have a more specific statutory guidelines to serve as reference points for the courts in appropriate cases when dealing with issues of lifting of the corporate veil especially between holding and subsidiary Companies.